SELECTION OF ALTERNATIVES FOR OIL FIELD DEVELOPMENT BY GENETIC ALGORITHMS - Túpac, Yvan J.; Vellasco, Marley Maria B.R.; Pacheco, Marco Aurélio C. (Revista de Engenharia Térmica, 2002)
This paper presents a Genetic Algorithm application for selecting the best alternative for oil field development under certainty. The alternatives in this study are related to the arrangement of wells in a known and delimited oil reservoir and serve as a basis for calculating the net present value, which is used to assess the optimization process: the optimal alternative is the one that maximizes the Net Present Value of the field. The results obtained have revealed that the Genetic Algorithm model was able to find good alternatives for the oil field development, achieving good results for the Net Present Value.